Efektivitas Pelaksanaan Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil pada Dinas Pendidikan dan Kebudayaan Kabupaten Belu - Maria De Fatima Barros; Saryono Yohanes; Yoh. G. Tuba Helan (Universitas Sains dan Teknologi Komputer, 2024)
The implementation of Government Regulation Number 94 concerning Civil Servant Discipline at the Belu Regency Education and Culture Office has not been fully effective where there are still violations of civil servant discipline including violations of time discipline and work discipline such as arriving late, leaving early, leaving the office and work for personal interests. The problems in this thesis are (1) How is the Effectiveness of the Implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline at the Belu Regency Education and Culture Office? (2) What are the Factors that hinder the Effectiveness of the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline at the Belu Regency Education and Culture Office? This research is a normative legal research supported by empirical legal research where the data is obtained directly from the research location by observation and interviews. to compare the applicable regulations with the reality that occurs in society and use qualitative descriptive juridical analysis. The results of this study indicate that (1) the local government of Belu Regency has provided TPP (Income Improvement Allowance) as an appreciation from the government, especially from the leader of the region related to work discipline. where employees who are absent are not in accordance with the provisions of working hours, the TPP of these employees is automatically deducted by the electronic attendance system, namely vinzer print, provisions like this, the local government has tried to maintain discipline within the scope of the State Civil Apparatus in carrying out its duties and obligations, but the system that has been implemented by this local government does not rule out the possibility of violations of discipline. These violations make the application of a provision or regulation in an agency not run effectively. (2) Factors inhibiting the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline at the Education and Culture Office of Belu Regency, namely: civil servant awareness factors, and cultural factors.